FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN DIARE DI KELURAHAN KULIM PUSKESMAS TENAYAN RAYA - Seprina, Zurni (Jurnal Keperawatan Priority, 2020)
Diarrhea is the number one cause of death worldwide. Data for 2017 states, nearly 1.7 billion cases of diarrhea occur in children with a mortality rate of around 760.000 in children under five each year WHO (2017). seconds one child dies of diarrhea. The purpose of this study was to determine the factors associated with the occurrence of diarrhea in the community. The design of this study was a quantitative study with a cross-sectional approach, with a sample of 50 respondents taken by saturated sampling technique. The results of the study are the relationship of clean water sources (p value = 0.001), family latrines (p value = 0.012), waste management (p value = 0.024), to the incidence of diarrhea in the community in RT 02 RW 03 Kulim Village Work Area Puskesmas Tenayan Raya Kota Pekanbaru with the stipulation of p value (<0.05) thus it can be concluded that the source of clean water, family latrines, and waste management are related to the incidence of diarrhea. The suggestion of the results of this study is that the people who become respondents can recognize and understand the clean environment in order to avoid diseases caused by damage to the environment that is less healthy.